Old-age pensions and female labour supply in India - Vidhya Unnikrishnan; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Whether cash transfers have unintended behavioural effects on the recipient household's labour supply is of considerable policy interest. We examine the 'intent to treat effect' of the Indira Gandhi National Old-Age Pension Scheme on prime-age women's labour supply decisions in India, where female labour force participation continues to decline over time. We find that having a pension-eligible individual in the household increases the probability of working by 3.2 percentage points for women aged 20-50, with the effect stronger for urban women. The effect is particularly strong if the pension-eligible individual is female. We provide suggestive evidence that this positive effect results from the income effect of the scheme, leading to reduced labour supply by the elderly, allowing them to provide greater childcare support. The increase in women's labour force participation is mostly in flexible employment, e.g. self-employment and agricultural and non-agricultural wage employment, and is particularly evident for poorer households.
Keywords: I38; J22; O15; 330; childcare; employment; income effect; labour supply; pension; women